2018
DOI: 10.7759/cureus.2750
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium Chimaera: A Rare Presentation

Abstract: Mycobacterium chimaera is an indolent nontuberculous mycobacterium which is abundant in soil, dust, and water. Although lacking recognition garnered by other mycobacteria (i.e., M. tuberculosis), it has been recognized as an emerging opportunistic threat to patients undergoing coronary bypass surgery and open heart procedures requiring extracorporeal devices. Here, we present a case of an individual initially seen in the inpatient setting without a history of such procedures or other risk factors commonly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Because Mycobacterium sp. are commonly found in soil, dust, and water [36], the bacterial contamination in the DNA may come from plant surfaces, but some studies have also shown that they may be endophytes in plants [37][38][39]. Some evidence suggests that endophytes may have a positive effect on plants [40,41], but Mycobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Because Mycobacterium sp. are commonly found in soil, dust, and water [36], the bacterial contamination in the DNA may come from plant surfaces, but some studies have also shown that they may be endophytes in plants [37][38][39]. Some evidence suggests that endophytes may have a positive effect on plants [40,41], but Mycobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…First identified in 2004, M. chimaera was responsible for a global outbreak linked to contaminated heater-cooler devices used in cardiac bypass surgery [8,9]. With a 50-60% mortality rate and prolonged treatment regimen of 12-18 months with an antibiotic cocktail of macrolides, ethambutol and rifamycins, new, better tolerated and more rapidly effective regimens are required [10].…”
Section: Introductionmentioning
confidence: 99%
“…Bills et al in 2009 describes a patient with a history of COPD and smoking [4]. A case report by Miskoff et al in 2018 described one patient presenting with underlying COPD [5]. The reason so few cases of patients with the underlying pulmonary disease have been reported may be due to its recent classification.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory disease outbreaks are linked to the formation of biofilms in heated stagnant water, which is a favorable environment for the pathogen [2,3]. Other NTB pathogens are associated with patients with underlying pulmonary disease, but this has only been seen in case reports regarding Mycobacterium chimaera specifically [1,4,5].…”
Section: Introductionmentioning
confidence: 99%